Teaching Strategies for Cooperative Learning for Effectiveness of Harmony Skills in Group Piano - Zhenyu, Yang; Suttachitt, Narutt (Journal of Ecohumanism, 2024)
Purpose: This study aims to develop a music learning strategy for teaching harmony in group piano lessons to promote harmonic skills. Method: Survey and interview music teachers in China and analyze data by content and thematic analysis. Findings: Teachers' assessment of cooperative learning strategies in harmonious teaching showed overall positive results. In particular, teachers generally agreed with the aspects of facilitating interaction, organization and management, cooperative skills, cooperative atmosphere and teacher's role. This suggests that the use of cooperative learning strategies in group piano classrooms is a recognized and effective teaching method. Individual teacher characteristics, especially teachers' gender, age, and educational background, significantly influenced the selection of cooperative learning strategies. Students gave positive comments on the skill level, musical expression, harmonic understanding, collaborative coordination, and learning interest in teaching harmony. Individual characteristics of students such as gender, age, and grade level have an impact on their assessment of the effectiveness of teaching and learning. The use of more comprehensive and targeted cooperative learning strategies is associated with higher levels of teaching effectiveness in group piano programs. Conclusion: The use of more comprehensive and targeted cooperative learning strategies is associated with higher levels of teaching effectiveness in group piano programs. This guides music educators and emphasizes the critical role of strategy selection in improving teaching effectiveness.